The Combined Approach of Teaching at the Right Level and Problem-Based Learning to Foster Mathematical Critical Thinking Skills - Sintawati, Mukti; Nurrohmah, Anisa; Feruzi, Sadiki Moshi; Abdurrahman, Ginanjar (The Indonesian Institute of Science and Technology Research, 2025)
Mathematical critical thinking is an essential skill that helps students analyze information, evaluate arguments, and solve complex problems systematically. However, many elementary students still struggle to attain higher-order thinking skills, mainly due to learning gaps in the classroom. This study aims to examine the effect of the integrated Teaching at the Right Level (TaRL) and Problem-Based Learning (PBL) approach on improving students' mathematical critical thinking skills. This research used a quasi-experimental method involving 34 fourth-grade students divided into experimental and control groups. The experimental group received TaRL–PBL instruction, while the control group used PBL only. Critical thinking skills were measured using pretest and posttest essay questions based on five indicators: interpretation, analysis, inference, evaluation, and explanation. The results showed a significant improvement in the experimental group (t = 2.462, p < 0.05) with a large effect size (Cohen’s d = 0.846), indicating that the TaRL–PBL approach had a strong impact on enhancing critical thinking. These findings suggest that integrating level-based instruction and problem-solving is effective in supporting differentiated learning and strengthening critical thinking in mathematics. The study also indicates that this integrated approach has strong potential to be further developed in mathematics education, particularly to enhance other skills such as creative thinking and mathematical connections.